Oracle Enterprise Manager Cloud Control 12c : managing data center chaos - Havewala, Porus Homi (Packt Publishing, 2012)
This book is a practical step-by-step tutorial with screenshots for carrying out tasks showing you how to manage and administer your data center with Oracle Enterprise Manager. It is packed with best practices and tips that will help you benefit from the author's extensive experience of working with Oracle Enterprise Manager since at least a decade, and combined with his 25+ years IT industry experience. If you are a Data Center, IT or Database Team manager who wants to take advantage of the automation and compliance benefits of Enterprise Manager 12c Cloud Control, then Oracle Enterprise Mana.